ISLAM AND GLOBALIZATION: AN EFFORT ON POSITIONING ISLAM IN GLOBAL TRANSFORMATION - Miftahuddin Miftahuddin Miftahuddin; Sukron Ma'mun Ma'mun (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2020)
The object of this article is to explore how different Muslim groups are responding globalization and how a globalization impacts on Muslim life. This is library research with the sociology of religion as the main perspective. There are four Muslim types on responding of globalization, namely a traditionalist, a liberal modernist, a fundamental revivalist, and an Islamist-transform. The uniqueness of the study is not only how the four Muslim groups respond on globalization, but also the contestation among the groups in a public space.